2013
DOI: 10.1111/ddi.12162
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble distribution models in conservation prioritization: from consensus predictions to consensus reserve networks

Abstract: Retaining information about the variation in the predicted distributions throughout the conservation prioritization seems to provide better results than summarizing the predictions before conservation prioritization. Our results highlight the need to understand and consider model-based uncertainty when using predicted distribution data in conservation prioritization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 49 publications
(69 reference statements)
2
79
0
2
Order By: Relevance
“…The relative contribution of individual patches to the regional connectivity depends on multiple factors, and only by accounting for these divergent conservation criteria can a good balance between the current and future habitat and connectivity requirements of all species within the network be ensured (Meller et al. ). We found that conserving connectivity and habitat quality for multiple species requires substantial increases in total habitat area protected and efficient prioritization of the habitat to be protected based on multiple criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of individual patches to the regional connectivity depends on multiple factors, and only by accounting for these divergent conservation criteria can a good balance between the current and future habitat and connectivity requirements of all species within the network be ensured (Meller et al. ). We found that conserving connectivity and habitat quality for multiple species requires substantial increases in total habitat area protected and efficient prioritization of the habitat to be protected based on multiple criteria.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the uncertainties of each statistical model and improve predictions of the current distribution of a species (Araújo, Whittaker, Ladle, & Erhard, ; Marmion, Parviainen, Luoto, Heikkinen, & Thuiller, ), we did an ensemble of five ENMs to assess the agreement or disagreement of their predictions. Combining ENMs within an ensemble could add information not shown in one single algorithm (Meller et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…biological invasions, V aclav ık & Meentemeyer, 2012; reserve designs, Meller et al, 2014), particularly for the prediction of the effect of climate change on biodiversity (Wiens et al, 2009;Franklin, 2010Franklin, , 2013Dawson et al, 2011;Bellard et al, 2012). biological invasions, V aclav ık & Meentemeyer, 2012; reserve designs, Meller et al, 2014), particularly for the prediction of the effect of climate change on biodiversity (Wiens et al, 2009;Franklin, 2010Franklin, , 2013Dawson et al, 2011;Bellard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%